The Influence of Price and Product Quality on Customer Satisfaction at Bakwan Andika MSMEs in Sidoarjo - Nadhya Meri Mustikadewi; Jimmy Ignatius; Ageng Pratiwi (Escalate : Economics and Business Journal, 2026)
Increasingly fierce competition in the culinary MSME sector requires business actors to implement pricing strategies and maintain product quality to increase customer satisfaction. This study aims to analyze the effect of price and product quality on customer satisfaction at Bakwan Andika UMKM in Sidoarjo. The study used a quantitative approach with a survey method, involving 55 respondents selected through a purposive sampling technique. Data were collected using a questionnaire and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, and t-tests and F-tests. The results showed that price and product quality each had a positive and significant effect on customer satisfaction, and simultaneously both variables also had a significant effect on customer satisfaction. The coefficient of determination (R²) value of 83.3% indicates that variations in customer satisfaction can be explained by price and product quality variables, while the remaining 16.7% is influenced by other factors outside the research model. These findings indicate that pricing that is in accordance with the value received by customers and consistency in maintaining product quality are important factors in increasing customer satisfaction. Therefore, MSMEs need to optimize these two aspects as a strategy to maintain competitiveness and encourage business sustainability.